If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 = 71 Reorder the terms: 10 + 3x = 71 Solving 10 + 3x = 71 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 3x = 71 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = 71 + -10 3x = 71 + -10 Combine like terms: 71 + -10 = 61 3x = 61 Divide each side by '3'. x = 20.33333333 Simplifying x = 20.33333333
| -6z+8-4=25 | | 4.2=2.7+h | | 8x-11+x=3+4x-19 | | 5y-1+21=6y+20-3y | | 3x-18=2x+10 | | 4x+3y=292 | | 9t-5=4t+10 | | h=16t^2+14 | | -21-9h=-3(4h+5) | | [7+(-3)]+(-5)=7+[(-3)+(-5)] | | 30-7m+10-3m= | | 2x+2*2x+7=2x+7 | | -21-9h= | | (X+28)=(3x+14) | | 260-64-9= | | (2/7)÷N=(5/7) | | 9.8k+3.7=-0.22 | | a^2-4a+4-b^2= | | y=3e^5x | | 3/4(x-6)=2/8(x+2) | | y^2-16x-64=0 | | 38*x^3+19x^2-158=0 | | R=D-TforD | | .5x-2=.3x+1.2 | | -4c+3-6c=34 | | -x+4x=40 | | 2log(x-5)=6 | | Z/12=12/4 | | X/12=59/60 | | y=-3x^2-6(3)-5 | | 3/w=18/42 | | x^2+4m-12=0 |